Pengaruh Terpaan Promosi Penjualan dan Brand Image terhadap Keputusan Pembelian di Shopeefood - Reichan Anantyo, Muhamad; Setyabudi, Djoko; Pradekso, Tandiyo (Interaksi Online, 2024)
In line with the rapid growth of the Online Food Delivery (OFD) industry, ShopeeFood entered the Indonesian market as a new competitor in 2021. Since its inception, ShopeeFood has offered a diverse range of sales promotions. Additionally, the platform successfully built a favorable brand image, evident in the increased ShopeeFood brand index in 2022. However, in 2022, ShopeeFood experienced a decline in sales figures. The theory employed to elucidate the impact of sales promotion exposure on purchasing decisions is Operant Conditioning, while the Consumer-Based Brand Equity Theory is used to explain the influence of brand image on purchasing decisions. This research involved respondents aged 17-40 in Jabodetabek exposed to ShopeeFood promotions. Regression analysis results indicate that sales promotion exposure has a significance value of 0.001 with a positive coefficient of 0.030, and brand image significance is 0.002 with a positive coefficient of 0.048. The conclusion emphasizes the importance for ShopeeFood to leverage sales promotion strategies and maintain brand image to enhance sales.